تبولوجيا CoKc - (Latakia University Journal -Basic Sciences Series, 2018)
يقال عن فضاء تبولوجي  إنه فضاء  إذا كانت كل مجموعة متراصة فيه مجموعة مغلقة, ويقال عن فضاء تبولوجي  إنه فضاء  أصغري( ) إذا كان  فضاء  وكان من أجل أية تبولوجيا على  مثل   و بحيث   لا يكون  فضاء . لقد قمنا في هذا البحث بدراسة - تبولوجيا والعلاقة بين - تبولوجيا و - تبولوجيا. Let  be a topological space,we say that  is -space if every compact subset of  is closed in , -space is called  Minimal - space   if every topology of such that  implies   is not a     -space. In this research we will study -topology and the relation between -topology and -topology.